Long Non-Coding RNAs in Thyroid Cancer - H. El Emam, Nour El Hoda; Sliem, Hamdy; M. Rashad, Nearmeen; Greash, Mohamed Ahmed; El Sherif, Iman (Journal of Neonatal Surgery, 2025)
Background: Accurate preoperative differentiation between benign and malignant thyroid nodules remains a clinical challenge, particularly in cases with indeterminate cytology. Conventional diagnostic tools such as ultrasound and fine-needle aspiration cytology have limited diagnostic accuracy in a subset of patients. Long non-coding RNAs, including Nuclear Enriched Abundant Transcript 1 (NEAT1), have emerged as potential molecular biomarkers in various malignancies, including thyroid cancer. Method: This observational cross-sectional study included sixty adult participants divided into three equal groups: patients with malignant thyroid nodules, patients with benign thyroid nodules, and healthy controls. Serum samples were collected from all participants. NEAT1 expression levels were quantified using quantitative real-time polymerase chain reaction and analyzed in serum. Statistical analysis and receiver operating characteristic (ROC) curve analysis were performed to assess the diagnostic performance of NEAT1 expression. Result: NEAT1 expression levels in serum was significantly higher in patients with malignant thyroid nodules compared with benign nodules and controls (p < 0.001). Serum NEAT1 expression showed a strong positive correlation. ROC curve analysis demonstrated high diagnostic accuracy of NEAT1 expression. Conclusion: NEAT1 is significantly upregulated in malignant thyroid nodules and demonstrates strong diagnostic performance. Circulating NEAT1 may serve as a promising non-invasive molecular biomarker to complement conventional diagnostic tools in the preoperative evaluation of thyroid nodules.